2023
DOI: 10.1002/bies.202300046
|View full text |Cite
|
Sign up to set email alerts
|

BENDing with Polycomb in pluripotency and cancer

Abstract: Three recent publications on BEND3 firmly establish its role as a novel sequencespecific transcription factor that is essential for PRC2 recruitment and maintenance of pluripotency. Here, we briefly review our current understanding of the BEND3-PRC2 axis in the regulation of pluripotency and also explore the possibility of a similar connection in cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…A possible tumor suppressor, HACE1 has been reported at this locus [72]. These observations strongly suggest that BEND3 may play an important role in cancer development and progression, also supported by a recent study which reports higher BEND3 expression in cancer cells across TCGA database compared with normal cells [13].…”
Section: Discussion and Future Prospectssupporting
confidence: 58%
See 2 more Smart Citations
“…A possible tumor suppressor, HACE1 has been reported at this locus [72]. These observations strongly suggest that BEND3 may play an important role in cancer development and progression, also supported by a recent study which reports higher BEND3 expression in cancer cells across TCGA database compared with normal cells [13].…”
Section: Discussion and Future Prospectssupporting
confidence: 58%
“…In a recent study, Abid et al compared the expression of PRC2 complex protein EZH2 and BEND3 across all the reported cancers in TCGA database and established a very strong correlation between the mRNA expression of these two. The correlation was even greater in breast cancer and in glioblastoma [13]. Furthermore, it also causes transcriptional repression of p21, a cell-cycle checkpoint protein, and arrests the cell cycle in the G1 or G2 phase, suggesting its possible oncogenic role.…”
Section: Discussion and Future Prospectsmentioning
confidence: 98%
See 1 more Smart Citation